Mitochondrial genome of Cordyceps blackwelliae: organization, transcription, and evolutionary insights into Cordyceps - Yong-Jie Zhang; Xiang-Ping Fan; Jia-Ni Li; Shu Zhang (IMA Fungus)
Abstract Cordyceps is a diverse genus of insect pathogenic fungi, with about 180 accepted species, including some well-known ones used as ethnic medicine and/or functional food. Nevertheless, mitogenomes are only available for four members of the genus. The current study reports the mitogenome of Cordyceps blackwelliae, a newly described entomopathogenic fungus. The 42,257-bp mitogenome of the fungus encoded genes typically found in fungal mitogenomes, and a total of 14 introns inserted into seven genes, including cob (1 intron), cox1 (4), cox3 (3), nad1 (1), nad4 (1), nad5 (1), and rnl (3). RNA-Seq analysis revealed differential expression of mitochondrial genes and supported annotations resulting from in silico analysis. There was clear evidence for polycistronic transcription and alternative splicing of mitochondrial genes. Comparison among mitogenomes of five different Cordyceps species (i.e., C. blackwelliae, C. chanhua, C. militaris, C. pruinosa, and C. tenuipes) revealed a high synteny, with mitogenome size expansion correlating with intron insertions. Different mitochondrial protein-coding genes showed variable degrees of genetic differentiation among these species, but they were all under purifying selection. Mitochondrial phylogeny based on either nucleotide or amino acid sequences confirmed the taxonomic position of C. blackwelliae in Cordycipitaceae, clustering together with C. chanhua. This study promotes our understanding of fungal evolution in Cordyceps.